Comparison of Functional Disability in Patients of Knee Osteoarthritis (KOA), among Rural and Urban KOA Patients - Ahmad, Zubair; Ahsan ilyas; Salman Latif; Maqsood, Umer; Jurat Ali (International Health Review, 2026)
Osteoarthritis (OA) is a chronic multifactorial disease that leads to progressive functional disability. The objective of the current research was to compare the functional disability in patients of Knee Osteoarthritis (KOA), among rural and urban KOA patients. A total of n=104 participants were recruited through non-probability convenient sampling technique from different rural and urban areas of Lahore, Pakistan. Participants with diagnosed osteoarthritis of both genders with age range 40-55 were included in the study. Those who had medical issues other than KOA or recent history of trauma or any fracture were excluded from thisstudy. Knee Injury and Osteoarthritis Outcome Score (KOOS) was used as data collection tool. The data was analyzed by using SPSS. 22. The mean age of participants was 47±3.45 years And 3.45. In the current study, 24% participants were male and 76% were females. The study showed 2.23±1.07 in difficulty of life in rural areas and 2.28±.99 in urban areas. The rate of KOA in urban populations was determined to be higher. They showed significantly more symptom severity as compared to rural patients with KOA. Symptom severity tends to affect their activities, such as sports, daily living activities, and also compromises the quality of life significantly more than the rural targeted population.